A Path to Mitigating SNS Ad Avoidance: Tailoring Messages to Individual Personality Traits. Issue 2 (4th May 2019) - Dodoo, Naa Amponsah; Wen, Jing (Taylor)
Abstract: Consumers generally pay little attention to ads on social networking sites (SNSs) in parallel with the rise of SNS advertising. In fact, consumers' adoption of varied strategies, such as ad avoidance, to reduce their exposure to advertising messages appears to be on the rise. However, limited attention has been given to psychological determinants of consumers' propensity to engage in SNS ad avoidance. Using the big five personality traits as a framework, this study experimentally examines how SNS ad messages tailored to fit personality traits function to determine individuals' likely engagement in SNS ad avoidance. As predicted, messages that are tailored to match personality traits are influential in determining SNS ad avoidance. Specifically, extraversion, openness to experience, agreeableness, and neuroticism did influence SNS ad avoidance, with the exception of conscientiousness. Perceived relevance mediated the relationships between the personality traits, perceived intrusiveness, and SNS ad avoidance. Perceived intrusiveness also was positively related to SNS ad avoidance. Theoretical contributions and implications are discussed.